SHORT TERM EFFECT OF CLOSED MITRAL COMMISSUROTOMY ON MITRAL VALVE AREA - Rehman, Ziaur; Rashid, Abdul; Bari, Abdul; Mufti, Tariq; Rahman, Mohammad (Journal of Ayub Medical College Abbottabad, 2000)
Background: Closed mitral commissurotomy is still an effective procedure for mitral stenosis in the third world countries. We studied the short term effect of closed instrumental mitral commissurotomy on mitral valve area in 146 patients. Methods: Each patient had echocardiography preoperatively. one and six months postoperative for mitral valve area determination by planimetry and pressure half time. Results: 67.7% patients were females and 32.3% were males with age range of 8 to 60 years and mean age of 24.3 years. 89% were having pure mitral stenosis and 11% having associated other lesion like mild aortic regurgitation, mild mitral regurgitation or tricuspid regurgitation. Preoperatively 72.6% patients were in functional Class 111 and 27.4% were in FC-IV. Mitral valve area ranged from 0.55-1.0 cm2 with mean of 0.9 cm2 pre-operatively which increased from 1.2 cm2 to 2.8 cm2 with mean of 2.4 cm2. This remained same after six months except in two pulmonary artery pressure ranged from 35 to lit) mmHg with mean of 5040 mmHg which dropped to 30 to 55 mmHg with mean of 358 mmHg at one month and 22 to 39 mmHg with mean of 27.7 mmHg at 6 months. Two patients could not be dilated and two patients developed acute mitral regurgitation for which they were subjected to mitral valve replacement in emergency. One patient died giving a mortality of 0.6%. Conclusions: We conclude that closed instrumental mitral commissurotomy is an effective economical and safe procedure for mitral stenosis.